2016
DOI: 10.1103/physrevb.93.180510
|View full text |Cite
|
Sign up to set email alerts
|

Coupled motion of Xe clusters and quantum vortices in He nanodroplets

Abstract: Single He nanodroplets doped with Xe atoms are studied via ultrafast coherent x-ray diffraction imaging. The diffraction images show that rotating He nanodroplets about 200 nm in diameter contain a small number of symmetrically arranged quantum vortices decorated with Xe clusters. Unexpected large distances of the vortices from the droplet center (≈0.7–0.8 droplet radii) are explained by a significant contribution of the Xe dopants to the total angular momentum of the droplets and a stabilization of widely spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 34 publications
4
41
0
Order By: Relevance
“…X-ray diffraction imaging of Xe doped He droplets revealed Bragg spots, confirming the existence of quantum vortex lattices that led to the condensation of 100-200 Xe clusters in a periodic array [18]. Positions and shapes of individual vortices could be deduced from diffraction images without Bragg spots by using a recently developed phase retrieval algorithm [19][20]. It was also found that about 50% of the droplets produce anisotropic diffraction patterns that can be described by concentric elliptic rings.…”
Section: Introductionmentioning
confidence: 79%
“…X-ray diffraction imaging of Xe doped He droplets revealed Bragg spots, confirming the existence of quantum vortex lattices that led to the condensation of 100-200 Xe clusters in a periodic array [18]. Positions and shapes of individual vortices could be deduced from diffraction images without Bragg spots by using a recently developed phase retrieval algorithm [19][20]. It was also found that about 50% of the droplets produce anisotropic diffraction patterns that can be described by concentric elliptic rings.…”
Section: Introductionmentioning
confidence: 79%
“…Angulons, on the other hand, are the eigenstates of the total angular momentum operator,L 2 , and therefore the transferred angular momentum is three-dimensional. While vortex instabilities have been subject to several experimental studies in the context of superfluid helium [4,5,[26][27][28][29][30][31], ultracold quantum gases [32][33][34][35][36], and superconductors [37][38][39][40], the transfer of angular momentum to a superfluid via the angulon instabilities has not yet been observed in experiment.In this Letter we provide evidence for the emergence of the angulon instabilities in experiments on CH 3 [41] and NH 3 [42] molecules trapped in superfluid helium nanodroplets. Spectroscopy of molecules matrix-isolated in 4 He has been an active area of research during the last two decades [6][7][8][9][10][11][12][13]43].…”
mentioning
confidence: 99%
“…The coupled motion of a vortex-dopant complex and decoupling conditions are studied. The reconnection of vortices, taken as an example of a fundamental process responsible for the evolution of a quantum turbulent state, is modeled to illustrate the difference between the light and heavy doping cases.Illuminating experiments in quantum turbulence were performed recently using superfluid helium nanodroplets [13][14][15][16]. Vortex filaments in rotating droplets were doped with Ag and Xe atoms and studied using a femtosecond x-ray coherent diffractive imaging technique as well as electron microscopy preceded by surfacedeposition of the samples.…”
mentioning
confidence: 99%
“…Several questions were raised in these works, including the origin of unusual shapes of doped helium droplets and distribution of vortices inside the droplet. Although certain aspects were clarified by theorists [17][18][19], the connection between the rotational motion of a droplet and a dopant still remains unclear [16]. In nanodroplet experiments doping particles are approximately 33 times heavier than fluid atoms and the diameter of each particle is comparable with a vortex core size in helium.…”
mentioning
confidence: 99%
See 1 more Smart Citation